HIGH TEMPERATURE GAS NITRIDING TREATMENT OF AISI 430 USING LOW AND HIGH PURITY NITROGEN GAS - Suprihanto, Agus (ROTASI, 2016)
The properties of stainless steels can be improved by high temperature gas nitriding (HTGN) treatment. The improving of their properties are obtained from nitrogen atom which diffuse into stainless steel. Nitrogen gas is the main source of nitrogen atom on the HTGN treatment. Generally, these treatment use high purity of nitrogen gas. The aim of this research is to investigate the effect of nitrogen gas purity on the HTGN treatment for AISI 430. Stainless steel AISI 430 plate 2 mm thick was processed by HTGN treatment. The specimens was exposed at nitrogen gas atmosphere at temperature 1200oC and held for 2 hours prior quenching in water. The treatment used industrial/welding grade (99.5%) as low nitrogen gas purity and ultra high purity (UHP) grade (99.999%) as high nitrogen gas purity. The vickers micro-hardness test was conducted to evaluate the hardness distribution from surface into middle section of the specimens before and after treatment. Light optical microscope was applied to examine the microstructure of specimens after treatment. Metallographic examination shows both treatments using low and high purity gas have the same grain size. However HTGN treatment using low purity of nitrogen gas produces hardness slightly lower than the high purity. This is due the high content of impurity of the low purity gas that reduces the partial pressure of nitrogen gas. Another effect of impurity is the reaction between nitrogen gas and its impurity especially oxygen gas. These reactions reduce the amount of free nitrogen atom which diffuses on the stainless steel.